Longitudinal Predictors of PROMIS Satisfaction With Social Roles and Activities After Shoulder and Knee Sports Orthopaedic Surgery in United States Military Servicemembers: An Observational Study. - Highland, Krista B.; Kent, Michael; McNiffe, Nicholas; Patzkowski, Jeanne C.; Patzkowski, Michael S.; Kane, Alexandra; Giordano, Nicholas A. (Orthopaedic Journal of Sports Medicine, 2023)
Background: Satisfaction with social roles and activities is an important outcome for postsurgical rehabilitation and quality of life but not commonly assessed. Purpose: To evaluate longitudinal patterns of the Patient-Reported Outcomes Measurement Information System (PROMIS) Satisfaction with Social Roles and Activities measure, including how it relates to other biopsychosocial factors, before and up to 6 months after sports-related orthopaedic surgery. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Participants (N = 223) who underwent knee and shoulder sports orthopaedic surgeries between August 2016 and October 2020 completed PROMIS computer-adaptive testing item banks and pain-related measures before surgery and at 6-week, 3-month, and 6-month follow-ups. In a generalized additive mixed model, covariates included time point; peripheral nerve block; the PROMIS Anxiety, Sleep Disturbance, and Pain Behavior measures; and previous 24-hour pain intensity. Patient-reported outcomes were modeled as nonlinear (smoothed) effects. Results: The linear (estimate, 2.06; 95% CI, 0.77-3.35; P =.002) and quadratic (estimate, 2.93; 95% CI, 1.78-4.08; P <.001) effects of time, as well the nonlinear effects of PROMIS Anxiety (P <.001), PROMIS Sleep Disturbance (P <.001), PROMIS Pain Behavior (P <.001), and pain intensity (P =.02), were significantly associated with PROMIS Satisfaction with Social Roles and Activities. The cubic effect of time (P =.06) and peripheral nerve block (P =.28) were not. The proportion of patients with a 0.5-SD improvement in the primary outcome increased from 23% at 6 weeks to 52% by 6 months postsurgery, whereas those reporting worsening PROMIS Satisfaction with Social Roles and Activities decreased from 30% at 6 weeks to 13% at 6 months. Conclusion: The PROMIS Satisfaction with Social Roles and Activities measure was found to be related to additional domains of function (eg, mental health, behavioral, pain) associated with postsurgical rehabilitation.